Employee effects on organizational outcomes: Korean travel industry - Heon Seo (Global Business & Finance Review (GBFR), 2022)
Purpose: This study aimed to identify the structural relationships among the self-efficacy, job satisfaction, organizational commitment, and customer orientation of travel agency employees in Seoul, Korea. Design/methodology/approach: Questionnaires were distributed to 250 potential respondents between February 1 and February 20 of 2020. The 225 valid cases were employees at travel agencies in Seoul. Data from the self-administered questionnaires were used to perform frequency, factor, and regression analyses. Findings: The study devised six hypotheses based on a review of the previous literature. The results found that self-efficacy positively influenced organizational commitment and job satisfaction, job satisfaction positively influenced customer satisfaction and organizational commitment, and self-efficacy and organizational commitment positively influenced customer orientation. Unlike previous studies, the validity and reliability of the constructs measuring the underlying factors were tested, and new measurement items were developed. The variation found among the statistical relationships provides support for strategic implications and fundamental data for personnel policies in the travel industry. Research limitations/implications: This study's respondents' self-efficacy was positively influenced by job satisfaction, organizational commitment, and customer orientation. Future studies may extend samples across the provinces in Korea for a comparative assessment of the results. Also, because the study focused on emotional commitment and do not consider other types of commitment, future studies should include measures of more of the dimensions of commitment to analyze relationships between organizational effectiveness and organization achievements. Originality/value: This study provides original and important results on the relationship between organizations and their employees.
Keywords: 650; Self-efficacy; job satisfaction; organizational commitment; customer orientation